PENGEMBANGAN MEDIA INTERAKTIF ARTICULATE STORYLINE PEMBELAJARAN BIOLOGI PENDEKATAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC) MATERI EKOSISTEM KELAS X SMA TERINTEGRASI NILAI-NILAI KEISLAMAN - fadhilaturrahmah, qonita; Muhfahroyin; Sujarwanta, Agus (BIOLOVA, 2024)
Abstrack: The development of interactive media Articulate storyline STEM (Science, Technology, Engineering, Mathematic) approach aims to facilitate students' learning to learn independently by using the Android they have in order to utilize Android and make it easier for students to understand the material so they can learn independently. Development uses the 4D model, namely define, design, develop, and disseminate. The result of the research is that the material expert validai is 4.58 and the percentage is 91.2%. As for design validation, the average for design validation was 4.61 and the percentage reached 92.2%. As for the validation of Islamic values, the average for validating Islamic values ​​was 4.8 and the percentage reached 96%. The results of the trial validation showed that the students' responses obtained an average score of 4.5 with a percentage of 90% and obtained test data. try small groups according to material aspects, namely 4.9 with a percentage of 98%, design aspects obtained an average of 4.48 with a percentage of 88%,” and aspects of the integration of Islamic values ​​obtained 4.8 with a percentage of 96%. the criteria show valid results with very good percentage criteria.